EFEKTIFITAS PAKET ASI (EDUKASI KESEHATAN : LAKTASI DAN PIJAT OKSITOSIN) TERHADAP PRODUKSI ASI IBU PRIMIPARA - Ulva Noviana (NHM PRESS, 2018)
Breast Milk (ASI) is the most perfectfood for the baby, where the nutritional contentin accordance with the need for intelligence.Breast milk contains antibody substances thatare useful for preventing infectious boweldisease and optimal digestion of growth anddevelopment. Based on the preliminary study ofNovember 2017 on 10 primiparous postpartumwomen, there were 7 postpartum mothersproducing less milk. The objectives of the studyanalyzed the differences in breast milkproduction in postpartum women before andafter being given a successful breastfeedingpackageThis study used pre experimental designwith one group pretest postest model ofindependent variables Package